Fast and Sensitive Method for Simultaneous Quantification of Meropenem and Vaborbactam in Human Plasma Microsamples by Liquid Chromatography-Tandem Mass Spectrometry for Therapeutic Drug Monitoring - Rossella Barone; Matteo Conti; Beatrice Giorgi; Milo Gatti; Pier Giorgio Cojutti; Pierluigi Viale; Federico Pea (MDPI AG, 2023)
Meropenem (MRP)-Vaborbactam (VBR) is a novel beta-lactam/beta-lactamase inhibitor used for the management of difficult-to-treat Gram-negative infections. Among critically ill patients, MRP-VBR shows remarkable inter-individual variability in pharmacokinetic behavior, thus justifying the implementation of therapeutic drug monitoring (TDM) for improving real-time management in different challenging scenarios. In this study, we developed and validated a fast and sensitive Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) method for the simultaneous quantification of MRP and VBR in human plasma microsamples of 3 microliters. The analysis required only a single-step sample preparation and was performed by means of a fast chromatographic run of 4 min, followed by positive electrospray ionization and detection on a high-sensitivity triple quadrupole tandem mass spectrometer operated in multiple reaction monitoring modes. The straightforward analytical procedure was successfully validated, based on the EMA guidelines, in terms of specificity, sensitivity, linearity, precision, accuracy, matrix effect, extraction recovery, the limit of quantification, and stability. The novel method was successfully applied for simultaneously measuring MRP and VBR concentrations in more than 42 plasma samples collected from critically ill patients affected by carbapenem-resistant Gram-negative bacteria infections.